DISEMINASI PRODUK JAGUNG SINTETIK UNHAS (SINHAS 1) DALAM PEMENUHAN KEBUTUHAN BENIH DAN PRODUKSI JAGUNG DI KABUPATEN TAKALAR - Farid, Muh.; Musa, Yunus; Jamil, Hatta; Ridwan, Ifayanti; Pati, Sakka; Nursini, .; Wahid, Abdul; Anshori, Muhammad Fuad (Jurnal Dinamika Pengabdian, 2020)
Drought and the availability of nitrogen fertilizers are the main constraints in the growth and production of maize, so it is necessary to build synthetic corn varieties that are tolerant of drought stress and low N fertilization. These synthetic maize varieties can support a wider planting of maize and involve farmers who lack capital, thus supporting increased production and national self-sufficiency in corn in a sustainable manner. The aim of the service was to introduce the Unhas Synthetic maize variety (SINHAS1) with dissemination and field meetings through the Experimental Demonstration Plots, as well as interviews about the level of farmers' preference for the SINHAS 1 variety. 2020. The activity was carried out through the socialization and dissemination process of SINHAS 1 corn through a pilot demonstration plot. The demonstration plot was carried out by combining the use of the superior varieties of SINHAS 1 corn with corn cultivation technology which is packaged as a corn cultivation technology package. The demonstration plot was conducted at four locations in Tarowang Village, Galesong Selatan District, Takalar Regency. The results of the activity showed that the level of farmers' preference for the Unhas synthetic maize variety (SINHAS 1) was very high (85%) with an average productivity of 7.8 tonnes / ha, so that it is very likely to be developed in Tarowang Village, Galesong Selatan District, Takalar Regency. Development efforts need socialization and dissemination on a broader scale to accelerate development efforts. Development efforts will be carried out together with the Tarowang Village-Owned Enterprises (BUMDes) in collaboration with the Faculty of Agriculture, Hasanuddin University to produce the SINHAS 1 corn variety through seed breeding. Keywords: Dissemination, corn, SINHAS 1, seed, takalar ABSTRAK Masalah kekeringan dan ketersediaan pupuk Nitrogen merupakan pembatas utama dalam pertumbuhan dan produksi jagung, sehingga diperlukan usaha perakitan varietas jagung sintetik yang toleran cekaman kekeringan dan pemupukan N rendah. Varietas jagung sintetik tersebut dapat menudukung penanaman jagung yang lebih luas dan melibatkan petani yang kurang modal sehingga mendukung peningkatan produksi dan swasembada jagung nasional secara berkelanjutan. Tujuan pengabdian adalah memperkenalkan varietas jagung Sintetik Unhas (SINHAS1) dengan diseminasi dan temu lapang melalui Demplot Percobaan, sekaligus wawancara tentang tingkat kesukaan petani terhadap varietas SINHAS 1. Kegiatan pengabdian dilaksanakan di Desa Tarowang, Kecamatan Galesong Selatan, Kabupaten Takalar yang berlangsung sejak Juli sampai Oktober 2020. Kegiatan dilakukan melalui proses sosialisasi dan diseminasi Jagung SINHAS 1 melalui Demplot Percobaan. Demplot dilakukan melalui perpaduan penggunaan varietas unggul jagung SINHAS 1 dengan teknologi budidaya jagung yang dikemas sebagai paket teknologi budidaya jagung. Demplot dilakukan pada empat lokasi yang ada di Desa Tarowang, Kecamatan Galesong Selatan, Kabupaten Takalar. Hasil kegiatan menunjukkan bahwa tingkat kesukaan petani terhadap varietas jagung sintetik Unhas (SINHAS 1) sangat tinggi (85%) dengan produktivitas rata-rata mencapai 7.8 ton/ha, sehingga sangat berpeluang dikembangkan di Desa Tarowang, Kecamatan Galesong Selatan, Kabupaten Takalar. Usaha pengembangan diperlukan sosialisasi dan diseminasi pada skala yang lebih luas untuk mempercepat usaha pengembangannya. Usaha pengembangan akan dilakukan bersama dengan Badan Usaha Milik Desa (BUMDes) Tarowang bekerjasama dengan Fakultas Pertanian Unhas untuk memproduksi varietas jagung SINHAS 1 melalui penangkaran benih. Kata Kunci: Diseminasi, jagung, SINHAS 1, benih, takalar.